PRESERVATION OF AN ANCIENT MANUSCRIPT COLLECTION IN THE AL-QUR'AN HISTORY MUSEUM OF NORTH SUMATRA - Miftahul Jannah Nasution; Yusra Dewi Siregar; Nabila Yasmin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The aim of this research is to determine the manuscript collection, preservation obstacles and solutions faced by the Al-Qur'an history museum in preserving ancient manuscripts. The research method used is qualitative research with a descriptive approach. The research subjects were staff who worked at the North Sumatra Al-Qur'an history museum. Primary data sources include the North Sumatra Al-Qur'an history museum, conducting interviews with several Al-Qur'an History museum staff regarding the research carried out. Data collection techniques: observation, interviews and documentation. Data analysis uses: Data Reduction, Data Presentation and Conclusion Drawing. Based on the research results obtained, it can be concluded that the results of the research are the collection of ancient manuscripts at the North Sumatra Al-Qur'an History Museum consisting of al-Qur'an manuscripts, fiqh manuscripts, tauhid, nahwu, tafsir, Sharaf, prayer manuscripts, manuscripts of mantiq, fawaid, mujarrobah, ushul fiqih, and manuscripts of the story of the prophet, as for the method of preserving ancient manuscripts in the North Sumatra Al-Qur'an history museum is by means of curative conservation and digitization, and the obstacles faced are the lack of conservators, funding, space adequate and conservation materials, and the solution for preserving the ancient manuscript collection at the North Sumatra Al-Qur'an History museum is to carry out routine preservation and maintenance with available materials, the museum recruits permanent conservators, carries out internal economic activities, and provides the collection in digital form.